Secondary School Students’ Cognitive Structure and Misconception in Respiration Topic - Mahror, Noraini; Diyana Mahmud, Siti Nur (Humanities & Social Sciences Reviews, 2020)
Purpose of the study: This study aims to explore the cognitive structures and identify the misconceptions experienced by secondary school students in the respiration topic. Methodology: This study is a qualitative study. The instruments used for data collection were the Word Association Test (WAT) and the Questionnaire of Writing Sentence (QWS). The data obtained were in word form. The breakpoint technique was used to analyze the data for WAT while the data for QWS were analyzed by category. Purposive sampling was applied in this study. A total of 23 forms four students comprising 12 boys and 11 girls participated in this study. Main Findings: The result showed that the students’ cognitive structures in the respiration topic were incomplete. The students were unable to form a comprehensive relationship for the given keywords, and there were also weak or incorrect associations. The misconceptions that had been identified are largely related to the keywords about cell respiration, anaerobic respiration, and breathing mechanism. Applications of this study: This study provides insights into the students’ cognitive structures and misconceptions about respiration. Thus, it will be useful for teachers in planning their teaching strategies so that they can improve the students’ cognitive structures as well as avoid misconceptions. Novelty: Most of the previous studies only focused on the identification of misconceptions without further investigation into the students’ cognitive structures, especially on the respiration topic. Thus, this study investigates the cognitive structures and misconceptions specifically among secondary school students who have learned respiration in biology.